Exploring perceptions, challenges, and opportunities of UDS health professionals’ students and faculty regarding community-based education programs for interprofessional education: A study protocol - Maxwell Ateni Assibi; Bruce Ayabilla Abugri; Patience Afua Adwaapa Karikari; Shamsu-Deen Ziblim; Victor Mogre (PLoS ONE, 2026)
Background Interprofessional education (IPE) is widely recognized as one of the critical approaches to ensuring that health professionals work together effectively to improve health outcomes. While community-based education (CBE) programmes have emerged as one of the promising approaches for IPE, there is little empirical evidence on how these programmes are received by students and faculty. At the University for Development Studies (UDS), the Third Trimester Field Practical Programme (TTFPP) and the Community-Based Education and Service (COBES) programme are some of the CBE programmes that offer student’s experiential learning. Aim This study aims to explore health professions students’ and faculty members’ perceptions, challenges, and opportunities associated with CBE programmes at UDS as platforms for IPE. Methods The research design for this study will be qualitative in nature and underpinned by an interpretive phenomenological approach. One-on-one interviews with purposively selected final-year health professions students and faculty members who have experienced TTFPP or COBES will be conducted. The data collected for the study will be analyzed using reflexive thematic analysis with the aid of qualitative data management software. Reflexivity, peer debriefing, and member checking will be some of the strategies used to ensure the research is of high methodological rigor. Expected outcomes The research is expected to produce contextualized understandings about the way in which CBE programmes are currently experienced in relation to IPE, including facilitators, constraints, and opportunities for more structured IPE.